Saga libertadores: independencia iberoamericana en el cine - Dr. José M. LAVÍN,Dr. Álvaro JIMÉNEZ SÁNCHEZ (Fonseca, Journal of Communication, 2023)
This research focuses on the Libertadores film saga produced by Iberoamerican producers in the last decade. This saga is composed by the films: Hidalgo, la historia Jamás contada (2010); Martí El ojo del canario (2010); San Martin. El cruce de los Andes (2011); Artigas:La Redota (2011); Bolívar. El hombre de las dificultades (2013); El niño rojo (2014); and Joaquim (2017). The methodology consists of an analysis focused on three sections: the character, history and allegorical aspects. The results show differences in the vision of the hero, various aesthetic and narrative treatments, and controversial approaches of the history of the Iberoamerican Independence